CHALLENGES AND COPING MECHANISMS OF SINGLE MOTHERS IN PAGSANJAN, LAGUNA AND STATUS OF WOMEN EMPOWERMENT: AN INPUT IN PROPOSED MODIFIED FRAMEWORK - Lorelyn Daanoy –Sagales,RSW, (EPRA International Journal of Research and Development (IJRD), 2023)
There were many cases of single mother in the Philippines rather than single father. It was because there were many females who were left behind while bearing the child which result to discrimination among society and lack of support emotionally and economically. Raising the child alone were a big responsibility since acted as resource provider to the needs of the child for education and daily living were essential. This descriptive-correlation study utilized 30 single mothers residing in Pagsanjan, Laguna. A researcher-made questionnaire was employed as an instrument to gather data and information necessary in this study. The statistical tools used were mean, standard deviation and regression analysis which was used to test the hypothesis. The findings of the study highlighted that single mother moderately encountered challenges in terms of financial support (M=3.25), work-life balance (M=3.17), emotional struggle (M=2.17) and decision making (3.01). Also, single mothers were involved in coping mechanism such as: physical (M=3.13), mental (M=3.26) and social (M=3.14). More so, women were highly empowered in terms of political (M=3.29), social(M=3.28) and health (M=3.25) while moderately empowered in terms of economic (3.19). From the data results of regression analysis, challenges encountered by single mother significantly predict women empowerment and coping mechanism of single parent significantly predict women empowerment having the p-value greater than .05 interpreted leads to the rejection of alternative hypothesis. Therefore, it is recommended for the collaboration and participation of different group of individual namely local government, department of social welfare and development, and other agencies with active participation from the women of community following the suggested framework by the researcher.